Potential secondary metabolite biosynthetic gene clusters and antibacterial activity of novel taxa Gandjariella - Fitria Ningsih; Dhian Chitra Ayu Fitria Sari; Shuhei Yabe; Akira Yokota; Wellyzar Sjamsuridzal (Society for Indonesian Biodiversity, 2020)
Abstract. Ningsih F, Sari DCAF, Yabe S, Yokota A, Sjamsuridzal W. 2020. Potential secondary metabolite biosynthetic gene clusters and antibacterial activity of novel taxa Gandjariella. Biodiversitas 21: 5674-5684. Microbial resistance to available antibiotics has gained increasing attention in recent years and led to the urgent search for active secondary metabolites from novel microbial taxa. This study aimed to assess putative secondary metabolite biosynthetic gene clusters (BGCs) in the genome of a novel thermophilic Actinobacteria type strain Gandjariella thermophila SL3-2-4T and screen for its antibacterial activity. Four other related novel candidate Actinobacteria strains, isolated from forest soil in the Cisolok geothermal area (West Java, Indonesia), were also screened for antibacterial activity in various media solidified with gellan gum. The genome of the SL3-2-4T strain contained 21 antiSMASH-identified secondary metabolite regions harboring BGCs. These BGCs were for polyketide synthase, non-ribosomal peptide synthase, and ribosomally synthesized and post-translationally modified peptide family clusters. Three BGC regions displayed 50-100% similarity with known secondary metabolites. Thirteen and five regions displayed low (4-35%) and no similarity with known BGCs for secondary metabolites, respectively. Strains SL3-2-4T and SL3-2-7 on MM 2 medium solidified with gellan gum at 45 °C for 14 days demonstrated inhibitory activity against all Gram-positive, but not Gram-negative bacteria. Strain SL3-2-10 on ISP 3 gellan gum medium incubated for seven days only active against K. rhizophila NBRC 12078. Strains SL3-2-6 and SL3-2-9 did not exhibit any antibacterial activity against the tested bacterial strains on the three tested media. The results indicated that novel taxa have the potential for the discovery of active secondary metabolites.